Spirit Hermeneutics or Biblical Interpretation by Any Other Name - Waddell, Robby; Keener, Craig S. 1960- (2018)
Within the guild of Pentecostal Studies, few topics have received more attention than biblical hermeneutics. Craig Keener, F.M. and Ada Thompson Professor of Biblical Studies at Asbury Theological Seminary, makes a significant contribution to this discussion with the publication of his book, Spirit Hermeneutics: Reading Scripture in the Light of Pentecost. Giving a priority to contextually sensitive, socio-historical methodologies, Keener attempts to define hermeneutics broadly in order to include most confessional perspectives. Indeed, he writes that Spirit Hermeneutics is Christian Hermeneutics. While such an inclusive move is admirable, it begs the question about the existence and viability of a distinctive hermeneutic for Pentecostals and Charismatics. This article reviews Keener’s argument and makes a case for a more distinctive hermeneutical theory.
Keywords: Hermeneutics -- Craig Keener -- Pentecostalism -- inspiration -- illumination; Rezension